Studying and analyzing the electrical network for Tulkarem - sawalmeh Moawya; Mohsen Ajwad (My University, 2020)
Electricity and power grids are very important elements in our world, it's not just about having lights or cocking or to have interest in our free time, electricity is very substantial resource especially in providing public security, safety and health and making possible everything from emergency response to medical care in hospitals, so it's very important to have a perfect electrical network without any problems or faults. Our project is about studying the electrical network of Tulkarem city and analyzing the problems related with the parameters of power system such as "current, voltage, power factor …… etc. " After that we will analysis the single line network on ETAP program to discover the problems and faults in the network. The main purpose of this project is to create some practical solutions for the problems we have forced in the network. In the second project we will provide a solar system to compensate the lack of electricity and we will study the effect of the system on the network.